PERSEPSI DAN PREFERENSI GENERASI Z TERHADAP APLIKASI MOBILE BANKING SYARIAH DI ERA DOMINASI FINTECH KONVENSIONAL - Mutiara Septyana; Fatimah Yunus; Gustiya Sunarti (Fakultas Ekonomi Universitas Prof. Dr. Hazairin, SH. Bengkulu, 2025)
This study aims to analyze Generation Z's perceptions and preferences regarding the use of sharia-compliant mobile banking applications amidst the dominance of conventional fintech. Using a descriptive qualitative approach, the study involved 10 Generation Z informants selected through purposive sampling. Data were collected through interviews, observation, and documentation, then analyzed using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The results show that Generation Z has a positive perception of sharia-compliant mobile banking, especially in terms of security and sharia compliance. However, their preference for conventional fintech is more dominant because it offers convenience, fast transactions, extensive integration with various digital platforms, and economic benefits such as cashback and promotions. This study also found a value-behavior gap, namely the difference between the understanding of sharia values ​​and the practice of using digital financial applications.